(3UdhGJ Ydi GdfHj Udi Gddg Ydjg hSdes - (3eMeO UGOb Hf Sdje GdYWGQs
(3ChdgG (B:s
(3CeG HYO agPg UdhGJ Ydi GdfHj Udi Gddg Ydjg hSde LdjdI s
(3BNQgG (B:s
(3hJbVj HgG MGLJj hYdi Bdg hUMHg hSde EfJgJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(506) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs